Reconnecting Theory and Practice in Pluralistic Contexts: Issues and Aristotelian Considerations. Issue 2 (April 2015) - Bredillet, Christophe N.; Tywoniak, Stephane; Dwivedula, Ravikiran
ABSTRACT The purpose of this article is to contribute, from a research practitioner perspective, to the theory–practice gap debate in organization studies, focusing on pluralistic contexts such as project organizing. The current debate is introduced; then the features of the two main philosophical traditions (i.e., modernism and postmodernism) are critically summarized. Then, propositions to reconnect theory and practice according to the Aristotelian premodern ethical and practical philosophy are discussed. Some key implications in the following areas are outlined: roles played by practitioners and scholars; emancipatory praxeological style of reasoning; closing the "phronetic gap"; and the development of "good practice, " ethics, and politics.